Static compression test of materials - Liu, Ruo Lin (Nanyang Technological University, 2023)
Static compression testing is one of the basic experiments to evaluate materials’ properties. The specimens of materials will be subjected to an increasing axial loads during the compression testing. After collecting the both stress and strain values from the tests, the stress-strain curve can be acquired, and thus the mechanical properties, including Yield Strength and Young’s Modulus, in the compression can be determined. Strictly following with the American Society for Testing and Materials (ASTM) International Standards, particularly the Standard Test Methods of Compression Testing of Metallic Materials at Room Temperature E9-19, especially for the specimen dimension and testing procedure that needs to be followed in order to attain a more accurate and precise test result. In this Final Year Project (B216), eight pieces of medium sized Aluminium Alloy 6061-T6511 solid cylindrical specimens with imperfect dimension are subjected to the static compression testing. By utilizing Shimadzu AG-Xplus 100kN testing machine, the Force-Displacement graph and Stress-Displacement graph will be attained from the TRAPEZIUMX software. In addition, by attaching the strain gauge on the surface of the specimen and connecting to the Data Logger, the strain values are collected from the TDS-7130 software. Hence, the Stress-Strain profile can be determined for the further analysis. After all the testing results are evaluated, the comparison with previous researchers’ results can be done and then the author enables to provide suggestions to the next researcher, for the purpose of improving accuracy and precision of the test results. Throughout the project, I have obtained the results, Yield Strength is 254.2 MPa and Young’s Modulus is 60.7 GPa. The percentage difference compared to literature values is -5.86%for Yield Strength and -11.94% for Young’s Modulus. By comparing to the previous researchers’ test results, It is not the most close values compared to literature values, the explanation will be illustrated in details, and the suggestions will also be provided as well as the experiment guidelines are about to be modified and enhanced.